The Long Road to Endometriosis Healthcare: The Experiences of Regional Women Living in Australia - Jessica Spain; Zalia Powell; Dimitra Lattas; Cindy Davis (Affilia, 2026)
Australian women's engagement with endometriosis healthcare can be a burdensome experience, with the time to diagnosis often delayed and prolonged engagement with healthcare due to the chronic nature of the disease. For regional women, their geographical location can create additional challenges to accessing endometriosis healthcare. This qualitative study explored the healthcare experiences of regional Australian women with endometriosis. In-depth semi-structured interviews were conducted with 22 women who lived in regional Australia at the time of their endometriosis diagnosis. Thematic analysis, informed by intersectionality and feminist theory, revealed three main themes of (1) Harder Healthcare in Regional Areas, (2) It Comes at a Cost, and (3) Acts of Resistance: Regional Resilience. These findings indicate that regional women with endometriosis draw on toughness and resilience to resist oppressive medical systems, whilst navigating intersectional layers of gender, age, financial, regional sociocultural and geographical disadvantage and privilege. Regional women's lived experiences of endometriosis-related healthcare is critical knowledge that can shape policy and practice to improve access to endometriosis healthcare in regional areas.